In the ruins of the Cold War bunker : affect, materiality and meaning making / edited by Luke Bennett. - Bennett, Luke (Place, memory, affect., 2017)
"This edited collection investigates the ways in which the physical remains of now abandoned military and civil defence bunkers from the Cold War have become the totems and sites of memory"--Provided by publisher.